RECOMMENDED FOODSTUFF SETS FOR NOURISHMENT OF PREGNANT WOMEN, NURSING MOTHERS AND INFANTS UNDER 3 YEARS OLD - article editorial (Педиатрическая фармакология, 2006)
(Педиатрическая фармакология. 2006; 3(5):68-75)